Prenatal and early-life exposure to micro- and nanoplastics and autism-relevant neurodevelopment: An integrated review of human, experimental, and mechanistic evidence - Jiyun Lee; Christie M. Sayes; Yunsong Mu; John P. Giesy; Hyeong-Moo Shin (Journal of Hazardous Materials, 2026)

The pandemic strain of the myrtle rust pathogen, Austropuccinia psidii, hosts multiple mycoviruses - Donald M. Gardiner; Stephen J. Fletcher; Rosalie Sabburg; Andrew D.W. Geering; Grant R. Smith; Madhuja Palaparambil Appukkuttan; Mu Sheen Chang; Thaís R. Boufleur; Chris A. Brosnan; Anne Sawyer (Fungal Biology, 2026)

Imaging orientation matters: Challenges in leaf area index measurement on slopes via levelled versus tilted photography - Yongkang Lai; Xihan Mu; Dasheng Fan; Jie Zou; Jing M. Chen; Weihua Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Soil-atmosphere terpene exchanges in the tropical forest of French Guiana with nitrogen and phosphorus fertilizer application - Kaijun Yang; Joan Llusià; Zhaobin Mu; Jordi Sardans; Catherine Preece; Iolanda Filella; Romà Ogaya; Albert Gargallo-Garriga; Guille Peguero; Laëtitia M. Bréchet; Clément Stahl; Leandro Van Langenhove; et al. (Plant and Soil, 2025)

Machine learning-accelerated determination of immunotoxicities of liquid crystal monomers - Jiawei Cheng; Yawen Yuan; Yunsong Mu; Fengchang Wu; Hyeong-Moo Shin; Christie M. Sayes; John P. Giesy (Journal of Hazardous Materials, 2025)

Eco-grease from upcycling of waste oils: a formulation study for high-performance lubricants - N. A. F. Bashari; M. A. A. Aziz; M. A. Hairunnaja; T. M. A. B. N. Mu’Tasim (International Journal of Environmental Science and Technology, 2025)
The disposal of waste oils, particularly waste engine oil (WEO) and waste turbine oil (WTO), presents serious economic and environmental issues due to their high contamination and degradation levels, which reduce the efficiency of direct reuse or conventional recycling. This study investigates a practical approach for upcycling WTO and WEO into high-performance lubricating grease, providing a sustainable substitute for petroleum-based lubricants. The study includes five essential stages: waste oil collection, pre-treatment, characterization, grease formulation, and performance assessment. Following treatment, the viscosity, elemental content, and moisture levels of the oils complied with Department of Environment (DOE) and ASTM D5185 standards, confirming their viability as base oils. The formulated greases achieved NLGI grades of 2–3, oil bleed percentages within a ± 15%, and oil separation below 4%. They also exhibited low coefficients of friction (0.062–0.133) and wear scar diameters ranging from 415.65 to 866 μm. These results confirm that treated WTO and WEO can be converted into greases with performance comparable to conventional products, supporting reduced dependence on virgin base oils. The formulations were assessed under relevant ASTM and NLGI standards. Future work may explore additives or scale-up approaches to enhance long-term performance and market readiness.

Effects of wilting duration and microbial inoculation on fermentation profile, chemical composition, aerobic stability and in situ nutrient degradability of ryegrass silage - F.X. Amaro; K.G. Arriola; L. Mu; S. Farooq; C. NinoDeGuzman; C. Romeiro; L.O. Lima; H. Sultana; A.O. Oyebade; M. Wallau; D. Vyas (Animal Feed Science and Technology, 2025)

Dynamics of water-soluble inorganic ions in Qinhuangdao: Particle size association and influences of environmental conditions - Ruihe Lyu; Ye Mu; Wenhua Wang; Xuefang Wu; Yao Ma; Roy M. Harrison (Urban Climate, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Improving Prediction of Intracranial Aneurysm Rupture Status Using Temporal Velocity-Informatics - M. Rezaeitaleshmahalleh; Z. Lyu; Nan Mu; Varatharajan Nainamalai; Jinshan Tang; J. J. Gemmete; A. S. Pandey; J. Jiang (Annals of Biomedical Engineering, 2025)

Urbanization exacerbates disparities in exposure to air pollution in China - Xiuling Zhao; Weiqi Zhou; Mu Hong; Andreas M. Neophytou (Environmental Research, 2025)

Exploring the synergistic effect of NaOH/NaClO absorbent in a novel wet FGD scrubber to control SOx/NOx emissions - Muhammad Rizwan; Muhammad Faryad Ali; Muhammad Asif Nawaz; Mu He; Yueqin Song; Peng Jiang; Saif Ullah; Malik M. Abdullah Hassan; Xiaolong Zhou (Environmental Monitoring and Assessment, 2025)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Bio-refinery of palm kernel expeller waste into attached microalgal biodiesel, the life cycle analysis of waste biomass-to-energy - Hemamalini Rawindran; Kuan Shiong Khoo; Ratchaprapa Raksasat; Chin Seng Liew; Wai Hong Leong; M. Devendran; Balasubramani Ravindran; Woei-Yenn Tong; Jin Chung Sin; Sze Mun Lam; Mu. Naushad; Jun Wei Lim (Process Safety and Environmental Protection, 2024)

Effects of neonicotinoid residues on non-target soil animals: A case study of meta-analysis - Yuxuan Cao; Wenting Zhao; Jinrui Zhang; Daniel M. Figueiredo; Mingyu Zhao; Siyang Ren; Hongyu Mu; Yiyi Li; Huan Lu; Haoyuan Shi; Xin Li; Jindong Li; et al. (Journal of Hazardous Materials, 2024)

Predicting the governing factors for the release of colloidal phosphorus using machine learning - Sangar Khan; Huimin Gao; Paul Milham; Kamel Mohamed Eltohamy; Habib Ullah; Hongli Mu; Meixiang Gao; Xiaodong Yang; Yasir Hamid; Peter S. Hooda; Sabry M. Shaheen; Naicheng Wu (Chemosphere, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

Chemo- and bio-stratigraphic constraints on Cretaceous-Paleocene biotic turnover in the southern Tethys low-oxygen margin, Egypt - Moataz El-Shafeiy; Daizhao Chen; Zhuyin Chu; Mu Liu; Ramadan M. El-Kahawy (Gondwana Research, 2024)

Association of prenatal exposure to PM2.5 and NO2 with gestational diabetes in Western New York - Kexin Zhu; Pauline Mendola; Vanessa M. Barnabei; Meng Wang; Rachael Hageman Blair; Joel Schwartz; James Shelton; Lijian Lei; Lina Mu (Environmental Research, 2024)

Seismic response of tripod suction bucket foundation for offshore wind turbine in sands - Xinglei Cheng; Yang Li; Kun Mu; M. Hesham El Naggar; Yadong Zhou; Piguang Wang; Xiaohan Sun; Ju Liu (Soil Dynamics and Earthquake Engineering, 2024)

Pesticide contamination remediation by biochar-immobilized microorganisms: a review - Y. Yang; X. Wang; Y. Wang; M. Saleem; Y. Mu; Y. Zheng; Q. Zhang (International Journal of Environmental Science and Technology, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

The behavior of strengthened and repaired RC columns with (CFRP) rope under different preloading levels - Ahmed M. Ashteyat; Ala’ Taleb Obaidat; Yasmeen Taleb Obaidat; Mu’atsem Abdel-Jaber; Dania Al-Tarawneh (European Journal of Environmental and Civil Engineering, 2023)

Indoor air pollution exposure and early childhood development in the Upstate KIDS Study - Alexandra Grippo; Kexin Zhu; Edwina H. Yeung; Erin M. Bell; Matthew R. Bonner; Lili Tian; Pauline Mendola; Lina Mu (Environmental Research, 2023)

Proteasomal Stimulation by MK886 and Its Derivatives Can Rescue Tau-Induced Neurite Pathology - Elly E. Liao; Mu Yang; Noah Nathan Kochen; Nagamani Vunnam; Anthony R. Braun; David M. Ferguson; Jonathan N. Sachs (Molecular Neurobiology, 2023)

Biochar-layered double hydroxide composites for the adsorption of tetracycline from water: synthesis, process modeling, and mechanism - Mukarram Zubair; Mohammad Saood Manzar; Amjad El-Qanni; Hajira Haroon; Hissah A. Alqahtani; Maryam Al-Ejji; Nuhu Dalhat Mu’azu; Jwaher M. AlGhamdi; Shamsuddeen A. Haladu; Dana Al-Hashim; Syed Z. Ahmed (Environmental Science and Pollution Research, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

A prospective observational phase IV study on effectiveness of animal derived polyclonal antibody antivenoms against West African carpet viper (Echis romani) induced coagulopathy and mortality - Titus B. Dajel; Saidu B. Abubakar; Nasiru M. Dan-Amarya; Nyam A. Azi; Salisu Mu'azu; Muhammad Hamza; Garba Iliyasu; Muhammad Y. Gwarzo; Abdulrazaq G. Habib (Toxicon, 2023)

Divergent structures of Mammalian and gammaherpesvirus uracil DNA glycosylases confer distinct DNA binding and substrate activity - Yunxiang Mu; Monika A. Zelazowska; Zaowen Chen; Joshua B. Plummer; Qiwen Dong; Laurie T. Krug; Kevin M. McBride (DNA Repair, 2023)

One-step calcination synthesis of 2D/2D g-C3N4/WS2 van der Waals heterojunction for visible light-induced photocatalytic degradation of pharmaceutical pollutants - Mario Vino Lincy Gnanaguru; Mu. Naushad; Tetiana Tatarchuk; Makarand M. Ghangrekar; Shamik Chowdhury (Environmental Science and Pollution Research, 2023)

Spatial attribution of declining Colorado River streamflow under future warming - Kristen M. Whitney; Enrique R. Vivoni; Theodore J. Bohn; Giuseppe Mascaro; Zhaocheng Wang; Mu Xiao; Mohammed I. Mahmoud; Chuck Cullom; Dave D. White (Journal of Hydrology, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Effect of shift work on frontline doctors’ mood and sleep during the COVID-19 pandemic - Susana Mu; Denise M. O’Driscoll; Rowan P. Ogeil; Alan C. Young (Sleep and Biological Rhythms, 2022)

Growth of non‐English‐language literature on biodiversity conservation - Shawan Chowdhury; Kristofer Gonzalez; M. Çisel Kemahlı Aytekin; Seung‐Yun Baek; Michał Bełcik; Sandro Bertolino; Sjoerd Duijns; Yuqing Han; Kerstin Jantke; Ryosuke Katayose; Mu‐Ming Lin; Elham Nourani; et al. (Conservation Biology, 2022)
English is widely recognized as the language of science, and English‐language publications (ELPs) are rapidly increasing. It is often assumed that the number of non‐ELPs is decreasing. This assumption contributes to the underuse of non‐ELPs in conservation science, practice, and policy, especially at the international level. However, the number of conservation articles published in different languages is poorly documented. Using local and international search systems, we searched for scientific articles on biodiversity conservation published from 1980 to 2018 in English and 15 non‐English languages. We compared the growth rate in publications across languages. In 12 of the 15 non‐English languages, published conservation articles significantly increased every year over the past 39 years, at a rate similar to English‐language articles. The other three languages showed contrasting results, depending on the search system. Since the 1990s, conservation science articles in most languages increased exponentially. The variation in the number of non‐English‐language articles identified among the search systems differed markedly (e.g., for simplified Chinese, 11,148 articles returned with local search system and 803 with Scopus). Google Scholar and local literature search systems returned the most articles for 11 and 4 non‐English languages, respectively. However, the proportion of peer‐reviewed conservation articles published in non‐English languages was highest in Scopus, followed by Web of Science and local search systems, and lowest in Google Scholar. About 20% of the sampled non‐English‐language articles provided no title or abstract in English; thus, in theory, they were undiscoverable with English keywords. Possible reasons for this include language barriers and the need to disseminate research in countries where English is not widely spoken. Given the known biases in statistical methods and study characteristics between English‐ and non‐English‐language studies, non‐English‐language articles will continue to play an important role in improving the understanding of biodiversity and its conservation.

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Productivity of Leymus chinensis grassland is co-limited by water and nitrogen and resilient to climate change - Yujie Shi; Yunna Ao; Baixin Sun; Johannes M. H. Knops; Jinwei Zhang; Zhihan Guo; Xianming De; Jiayu Han; Yuheng Yang; Xiaoyu Jiang; Chunsheng Mu; Junfeng Wang (Plant and Soil, 2022)

Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Samantha Morais; Adriana Costa; Gabriela Albuquerque; Natália Araújo; Claudio Pelucchi; Charles S. Rabkin; Linda M. Liao; Rashmi Sinha; Zuo-Feng Zhang; Jinfu Hu; Kenneth C. Johnson; Domenico Palli; et al. (Cancer Causes & Control, 2022)

Plant invasion alters latitudinal pattern of plant‐defense syndromes - Mu Liu; Yuanfei Pan; Xiaoyun Pan; Alejandro Sosa; Dana M. Blumenthal; Mark Van Kleunen; Bo Li (Ecology, 2021)
The relationship between herbivory and latitude may differ between native and introduced populations of invasive plants, which can generate latitudinal heterogeneity in the strength of enemy release. However, still little is known about how latitudinal heterogeneity in herbivore pressure influences latitudinal variation in defense phenotypes of invasive plants. We tested how latitudinal patterns in multi‐variate defense syndromes differed between native (Argentinian) and introduced (Chinese) populations of the invasive herb Alternanthera philoxeroides . In addition, to better understand the drivers underlying latitudinal patterns, we also tested whether associations of defense syndromes with climate and herbivory differed between native and introduced ranges. We found that native plant populations clustered into three main defense syndromes associated with latitude. In contrast, we only found two defense syndromes in the introduced range. One matched the high‐latitude syndrome from the native range, but was distributed at both the northern and southern range limits in the introduced range. The other was unique to the introduced range and occurred at mid‐latitudes. Climatic conditions were associated with variation in syndromes in the native range, and climatic conditions and herbivory were associated with variation in syndromes in the introduced range. Together, our results demonstrate that plants may under the new environmental conditions in the introduced range show latitudinal patterns of defense syndromes that are different from those in their native range. This emphasizes that geographical dependence of population differentiation should be explicitly considered in studies on the evolution of defense in invasive plants.

Transmission of SARS-CoV-2 virus and ambient temperature: a critical review - Yunsong Mu; Meichen Shao; Buqing Zhong; Yiqun Zhao; Kenneth M. Y. Leung; John P. Giesy; Jin Ma; Fengchang Wu; Fangang Zeng (Environmental Science and Pollution Research, 2021)

Human growth hormone proteoform pattern changes in pituitary adenomas: Potential biomarkers for 3P medical approaches - Biao Li; Xiaowei Wang; Chenguang Yang; Siqi Wen; Jiajia Li; Na Li; Ying Long; Yun Mu; Jianping Liu; Qin Liu; Xuejun Li; Dominic M. Desiderio; et al. (EPMA Journal, 2021)

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Assessing flood risk in Baiyangdian Lake area in a changing climate using an integrated hydrological-hydrodynamic modelling - Y. Wang; X. Zhang; Q. Tang; M. Mu; C. Zhang; A. Lv; S. Jia (Hydrological Sciences Journal, 2019)

WormBot, an open-source robotics platform for survival and behavior analysis in C. elegans - Jason N. Pitt; Nolan L. Strait; Elena M. Vayndorf; Benjamin W. Blue; Christina H. Tran; Brendon E. M. Davis; Karen Huang; Brock J. Johnson; Keong Mu Lim; Sophie Liu; Arash Nikjoo; Anuj Vaid; et al. (GeroScience, 2019)

Treatment of fluoride-contaminated water. A review - P. Senthil Kumar; S. Suganya; S. Srinivas; S. Priyadharshini; M. Karthika; R. Karishma Sri; V. Swetha; Mu. Naushad; Eric Lichtfouse (Environmental Chemistry Letters, 2019)

Chronic Nicotine Exposure Alters Metabotropic Glutamate Receptor 5: Longitudinal PET Study and Behavioural Assessment in Rats - Adrienne Müller Herde; Yoan Mihov; Stefanie D. Krämer; Linjing Mu; Antoine Adamantidis; Simon M. Ametamey; Gregor Hasler (Neurotoxicity Research, 2019)

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

Trade-offs and synergies between seed yield, forage yield, and N-related disservices for a semi-arid perennial grassland under different nitrogen fertilization strategies - Yujie Shi; Junfeng Wang; Xavier Le Roux; Chunsheng Mu; Yunna Ao; Song Gao; Jinwei Zhang; Johannes M. H. Knops (Biology and Fertility of Soils, 2019)

Representative agricultural pathways, climate change, and agricultural land uses: an application to the Pacific Northwest of the USA - Jianhong E. Mu; John M. Antle; John T. Abatzoglou (Mitigation and Adaptation Strategies for Global Change, 2019)

The Effect of a Medical Toxicology Inpatient Service in an Academic Tertiary Care Referral Center - Andrew M. King; Shooshan Danagoulian; Michael Lynch; Nathan Menke; Yijia Mu; Melissa Saul; Michael Abesamis; Anthony F. Pizon (Journal of Medical Toxicology, 2019)

An Evaluation of the Resilience of the Regional Agricultural Water and Soil Resource System in Heilongjiang Province, China - Dong Liu; Ran Mu; Qiang Fu; Chunlei Liu; Tianxiao Li; Khan M. Imran; Song Cui; Faiz M. Abrar (Agricultural Research, 2018)

Applications of nanocomposite hydrogels for biomedical engineering and environmental protection - Gaurav Sharma; Bharti Thakur; Mu. Naushad; Amit Kumar; Florian J. Stadler; Sulaiman M. Alfadul; Genene Tessema Mola (Environmental Chemistry Letters, 2018)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

RHEB1 insufficiency in aged male mice is associated with stress-induced seizures - Qi Tian; Pavel Gromov; Joachim H. Clement; Yingming Wang; Marc Riemann; Falk Weih; Xiao-Xin Sun; Mu-Shui Dai; Lev M. Fedorov (GeroScience, 2017)

Climate impacts on agricultural land use in the USA: the role of socio-economic scenarios - Jianhong E. Mu; Benjamin M. Sleeter; John T. Abatzoglou; John M. Antle (Climatic Change, 2017)

Increased productivity in wet years drives a decline in ecosystem stability with nitrogen additions in arid grasslands - Junfeng Wang; Johannes M. H. Knops; Chad E. Brassil; Chunsheng Mu (Ecology, 2017)
Adding nutrients to nutrient‐limited ecosystems typically lowers plant diversity and decreases species asynchrony. Both, in turn, decrease the stability of productivity in the response to negative climate fluctuations such as droughts. However, most classic studies examining stability have been done in relatively wet grasslands dominated by perennial grasses. We examined how nutrient additions influence the stability of productivity to rainfall variability in an arid grassland with a mix of perennial and annual species. Of the nutrients, only nitrogen increased productivity, and only in wet years. In addition, only nitrogen decreased the stability of productivity. Thus, nutrient addition makes ecosystem productivity less stable in both wet and arid grasslands. However, the mechanism is very different. In contrast to wet grasslands, adding nitrogen to an arid grassland did not decrease diversity. Rather, stability decreased with nitrogen addition due to an increase in annual species that increased productivity. In other words, in our arid grassland, nitrogen addition decreased ecosystem stability because of increased ecosystem responsiveness to positive climate fluctuations. These climate fluctuations were facilitated by annual species that take advantage of wet years and can escape dry years as seeds. Our data support the conclusion that nutrient additions decrease the stability of productivity in both wet and arid grasslands. Nutrient enrichment increases the sensitivity of productivity to low rainfall years in wet grasslands, whereas nutrient enrichment in arid grasslands increases the sensitivity of productivity to high rainfall years.

Pain, Sleep Disturbance, and Quality of Life Among Palestinian Patients Diagnosed with Cancer - Mu’taz M. Dreidi; Ayman M. Hamdan-Mansour (Journal of Cancer Education, 2016)

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease - Lijiang Ma; Yavuz Bayram; Heather M. McLaughlin; Megan T. Cho; Alyson Krokosky; Clesson E. Turner; Kristin Lindstrom; Caleb P. Bupp; Katey Mayberry; Weiyi Mu; Joann Bodurtha; Veronique Weinstein; et al. (Human Genetics, 2016)

Preparation of polyaniline based nanocomposite material and their environmental applications - R. Bushra; M. Shahadat; M. A. Khan; R. Adnan; M. Arshad; M. Rafatullah; Mu. Naushad (International Journal of Environmental Science and Technology, 2015)

Removal of BrO3 − from drinking water samples using newly developed agricultural waste-based activated carbon and its determination by ultra-performance liquid chromatography-mass spectrometry - Mu. Naushad; Mohammad R. Khan; Zeid A. ALOthman; Ibrahim AlSohaimi; Francisco Rodriguez-Reinoso; Turki M. Turki; Rahmat Ali (Environmental Science and Pollution Research, 2015)

Land use and management change under climate change adaptation and mitigation strategies: a U.S. case study - Jianhong E. Mu; Anne M. Wein; Bruce A. McCarl (Mitigation and Adaptation Strategies for Global Change, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Population pharmacokinetics of intravenous and oral panobinostat in patients with hematologic and solid tumors - Marina Savelieva; Margaret M. Woo; Horst Schran; Song Mu; Jerry Nedelman; Renaud Capdeville (European Journal of Clinical Pharmacology, 2015)

Simultaneous detection of perchlorate and bromate using rapid high-performance ion exchange chromatography–tandem mass spectrometry and perchlorate removal in drinking water - Danielle M. West; Ruipu Mu; Sanjeewa Gamagedara; Yinfa Ma; Craig Adams; Todd Eichholz; Joel G. Burken; Honglan Shi (Environmental Science and Pollution Research, 2015)

Solid Lipid Particles for Oral Delivery of Peptide and Protein Drugs III — the Effect of Fed State Conditions on the In Vitro Release and Degradation of Desmopressin - Philip C. Christophersen; Dimple Vaghela; Anette Müllertz; Mingshi Yang; Hanne M. Nielsen; Huiling Mu (The AAPS Journal, 2014)

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Relations between stimulation of mesolimbic dopamine and place conditioning in rats produced by cocaine or drugs that are tolerant to dopamine transporter conformational change - Gianluigi Tanda; Su Min Li; Maddalena Mereu; Alexandra M. Thomas; Aaron L. Ebbs; Lauren E. Chun; Valeria Tronci; Jennifer L. Green; Mu-Fa Zou; Theresa A. Kopajtic; Amy Hauck Newman; Jonathan L. Katz (Psychopharmacology, 2013)

Adaptation to climate change: changes in farmland use and stocking rate in the U.S. - Jianhong E. Mu; Bruce A. McCarl; Anne M. Wein (Mitigation and Adaptation Strategies for Global Change, 2013)

Microarray analysis of gene expression in peripheral blood leucocytes from rock bream (Oplegnathus fasciatus) after stimulation by LPS, ConA/PMA, and poly I:C - Mun-Gyeong Kwon; Ju-Won Kim; Myoung-Ae Park; Jee-Youn Hwang; Hye-Sung Choi; Mu-Chan Kim; Dae-Won Park; J.-M. Jung; Chan-Il Park (Genes & Genomics, 2013)

Adsorption of cadmium ion using a new composite cation-exchanger polyaniline Sn(IV) silicate: kinetics, thermodynamic and isotherm studies - Mu. Naushad; Z. A. AL-Othman; M. Islam (International Journal of Environmental Science and Technology, 2013)

Sequence characterization and promoter identification of porcine APC10 gene - W. B. He; Z. W. Wang; Y. Li; Z. L. Tang; S. L. Yang; Y. L. Mu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

Neuropsychiatric disorders related to interferon and interleukins treatment - Aye Mu Myint; Markus J. Schwarz; Harry W. M. Steinbusch; Brian E. Leonard (Metabolic Brain Disease, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

A black-streaked dwarf disease on rice in China is caused by a novel fijivirus - Heng-Mu Zhang; Jian Yang; Jian-Ping Chen; M. J. Adams (Archives of Virology, 2008)

Completion of the sequence of rice gall dwarf virus from Guangxi, China - Heng-Mu Zhang; Xing Xin; Jian Yang; Jian-Ping Chen; Jian-Ming Wang; M. J. Adams (Archives of Virology, 2008)

One-carbon metabolism gene polymorphisms and risk of non-Hodgkin lymphoma in Australia - Kyoung-Mu Lee; Qing Lan; Anne Kricker; Mark P. Purdue; Andrew E. Grulich; Claire M. Vajdic; Jennifer Turner; Denise Whitby; Daehee Kang; Stephen Chanock; Nathaniel Rothman; Bruce K. Armstrong (Human Genetics, 2007)

Classification of breast masses via nonlinear transformation of features based on a kernel matrix - Tingting Mu; Asoke K. Nandi; Rangaraj M. Rangayyan (Medical & Biological Engineering & Computing, 2007)

Interconversion Pharmacokinetics of Simvastatin and its Hydroxy Acid in Dogs: Effects of Gemfibrozil - Thomayant Prueksaritanont; Yue Qiu; Lillian Mu; Kimberly Michel; Janice Brunner; Karen M. Richards; Jiunn H. Lin (Pharmaceutical Research, 2005)

First records of the papaya strain of Papaya ringspot virus (PRSV-P) in French Polynesia and the Cook Islands - R. I. Davis; L. Mu; N. Maireroa; W. J. Wigmore; M. Grisoni; M. F. Bateson; J. E. Thomas (Australasian Plant Pathology, 2005)

Use of new EST markers to elucidate the genetic differences in grain protein content between European and North American two-rowed malting barleys - M. Moralejo; J. S. Swanston; P. Muoz; D. Prada; M. Ela; J. R. Russell; L. Ramsay; L. Cistu; P. Codesal; A. M. Casas; I. Romagosa; W. Powell; et al. (Theoretical and Applied Genetics, 2004)

Knowledge of post-exposure prophylaxis inadequate despite published guidelines - J. Parra-Ruiz; L. Muoz-Medina; J. Callejas-Rubio; M. Martnez; M. A. Martnez-Prez; J. Hernndez-Quero (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Pleural empyema due to Salmonella enteritidis in a non-immunocompromised patient - M. Len Lope; P. Batalha; M. Sosa; F. J. Rodrguez-Gmez; A. Snchez-Muoz; E. Pujol; J. M. Aguado (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

The Null method applied to GNSS three-carrier phase ambiguity resolution - U. Fernndez-Plazaola; T. M. Martn-Guerrero; J. T. Entrambasaguas-Muoz; M. Martn-Neira (Journal of Geodesy, 2004)

Metal Concentrations in Soil in the Vicinity of a Municipal Solid Waste Landfill with a Deactivated Medical Waste Incineration Plant, Ribeiro Preto, Brazil - S. I. Segura-Muoz; A. Bocio; T. M. B. Trevilato; A. M. M. Takayanagui; J. L. Domingo (Bulletin of Environmental Contamination and Toxicology, 2004)

Relevance of genetically determined host factors to the prognosis of meningococcal disease - P. Domingo; E. Muiz-Diaz; M.A. Baralds; M. Arilla; N. Barquet; R. Pericas; C. Jurez; P. Madoz; G. Vzquez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Trace Metal Distribution in Surface Soil in the Area of a Municipal Solid Waste Landfill and a Medical Waste Incinerator - S. I. Segura-Muoz; A. M. M. Takayanagui; T. M. B. Trevilato; C. B. Santos; S. E. Hering (Bulletin of Environmental Contamination and Toxicology, 2004)

Interaction between the noradrenergic and serotonergic systems in locomotor hyperactivity and striatal expression of Fos induced by amphetamine in rats - A. Muoz; A. Lopez-Real; J. L. Labandeira-Garcia; M. J. Guerra (Experimental Brain Research, 2003)

Estimation of Population Pharmacokinetic Parameters in the Presence of Non-compliance - Song Mu; Thomas M. Ludden (Journal of Pharmacokinetics and Pharmacodynamics, 2003)

Cellular redox state and activating protein-1 are involved in ascorbate effect on calcitriol-induced differentiation - G. Lpez-Lluch; M. -V. Blzquez; R. Prez-Vicente; A. Macho; M. I. Burn; F. J. Alcan; E. Muoz; P. Navas (Protoplasma, 2001)

Comparison of Particle Image Velocimetry and Laser Doppler Anemometry Measurements in Turbulent Fluid Flow - M. P. Wernet; A. Subramanian; H. Mu; J. R. Kadambi (Annals of Biomedical Engineering, 2000)

Cleistogamy inCentaurea melitensis (Asteraceae): Capitulum variability and spatio-temporal development patterns - R. Porras; J. M. Muoz (Plant Systematics and Evolution, 2000)

Expression of human muscarinic cholinergic receptors in tobacco - Jing-Hong Mu; Nam-Hai Chua; Elliott M. Ross (Plant Molecular Biology, 1997)

NF-?B activation by CD26 antigen is independent of dipeptidyl peptidase IV activity - M. V. Blzquez; C. Ortiz; E. Aranda; E. Collantes; A. Isral; E. Muoz (Protoplasma, 1997)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

Structure and expression inE. coli of the gene coding for protein p10 of African swine fever virus - M. Muoz; J. M. P. Freije; M. L. Salas; E. Viuela; C. Lpez-Otn (Archives of Virology, 1993)